Poesía comprometida: ¿un compromiso para la actualidad? - Alfons, Gregori i Gomis (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
The essay Littérature et engagement: De Pascal à Sartre, written by the Belgian Benoît Denis, presents several critical problems about poetry and commitment. In the present article we will analyze some of these questions taking into account some important points about the changing of connotations and interpretations on forms of poetry and on poetry itself in the last century. Furthermore, this process of analyzing will provide a reconsideration of nowadays approximations to committed poetry from the critical point of view.
Committed poetry: A real jam for present time?